2019
DOI: 10.3390/ani9100741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mannan Oligosaccharides on Gas Emission, Protein and Energy Utilization, and Fasting Metabolism in Sheep

Abstract: Simple SummaryMannan oligosaccharides (MOS) are a promising feed additive to improve animal health, immune capacity, and antioxidation. Based on the previous studies, we carried out three experiments to investigate the effects of MOS on the gas emission, protein and energy utilization, and fasting metabolism of sheep. The results showed that 2.0% MOS supplementation led to the lowest in vitro CO2 production and lower CH4 production and decreased in vivo intake. However, it also decreased urine nitrogen excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…Because supplementation dietary MOS brought long villi and shallow crypts which provided a larger surface area for nutrients absorption in small intestine of animals ( Chacher et al, 2017 ), and an our previous study also demonstrated that supplementation dietary MOS elongated the villus height and the muscular thickness, and decreased the villus width of lamb duodenum significantly ( Zheng et al, 2020 ), so, the monitoring results about supplementation dietary MOS improved nutrient digestion of sheep in the current study were observed. And some previous studies have reported similar results, with MOS increasing the digestion of NDF and ADF ( Zheng et al, 2018 ), and nitrogen retention in sheep ( Zheng et al, 2018 ; Zheng et al, 2019 ), as well as improving the nitrogen, zinc, and iron metabolism of calves and lambs ( Cole, Purdy & Hutcheson, 1992 ). However, another study reported that MOS did not affect nutrient digestibility in dairy cows ( Moallem et al, 2009 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Because supplementation dietary MOS brought long villi and shallow crypts which provided a larger surface area for nutrients absorption in small intestine of animals ( Chacher et al, 2017 ), and an our previous study also demonstrated that supplementation dietary MOS elongated the villus height and the muscular thickness, and decreased the villus width of lamb duodenum significantly ( Zheng et al, 2020 ), so, the monitoring results about supplementation dietary MOS improved nutrient digestion of sheep in the current study were observed. And some previous studies have reported similar results, with MOS increasing the digestion of NDF and ADF ( Zheng et al, 2018 ), and nitrogen retention in sheep ( Zheng et al, 2018 ; Zheng et al, 2019 ), as well as improving the nitrogen, zinc, and iron metabolism of calves and lambs ( Cole, Purdy & Hutcheson, 1992 ). However, another study reported that MOS did not affect nutrient digestibility in dairy cows ( Moallem et al, 2009 ).…”
Section: Discussionsupporting
confidence: 65%
“…In sheep, supplementation dietary MOS increased ruminal pH and total short chain fatty acids (SCFAs) concentration, decreased lipopolysaccharides (LPS) level in plasma, reduced ruminal ammonia concentration and ruminal stratum corneum thickness and total thickness of ruminal epithelium, as well as the incidence and severity of hepatic abscesses ( Diaz et al, 2018 ). In our previous studies, similarly, supplementation dietary MOS increased antioxidant capacity ( Zheng et al, 2018 ) and crude protein (CP) retention rate and decreased energy release as methane (CH 4 ) in sheep ( Zheng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 79%
“…A positive relationship between CO 2 and CH 4 in the current study agreed with those reported by Zheng et al 34 and Patra and Yu. 42 However, some studies have shown that there was a negative relationship, because CO 2 and H 2 are, in general, the precursors for CH 4 formation in the rumen.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that O 2 consumption was not affected due to the similarity of dry matter intake by the lambs. The unchanged RQ was expected as the sheep in the current study were fed ad libitum and feed intake was not affected 33,34 . An RQ greater than 1 is usually reported in trials with ruminants, as shown by Nichols et al 35 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation